House of cards [videorecording (DVD)] : the final season - Sakharov, Alik, 1959-; Mann, Ami Canaan; Wright, Robin, 1966-; Wright, Robin, 1966-; Kelly, Michael, 1969-; Lane, Diane (Sony Pictures Home Entertainment, 2019)
Claire Underwood becomes the first female president of the United States and must find a way to keep her power.